SOBRE DOS ESPECIES BRASILEÃ‘AS DEL GENERO â€œð˜Œð˜ð˜¢ð˜´ð˜®ð˜¶ð˜´â€ Insecta: Hymenoptera: Elasmidae - Santis, Luiz de (REVISTA DE AGRICULTURA, 2020)
SOBRE DOS ESPECIES BRASILEÃ‘AS DEL GENERO â€œð˜Œð˜ð˜¢ð˜´ð˜®ð˜¶ð˜´â€ Insecta: Hymenoptera: Elasmidae